MEKARSARI KELURAHAN ROWOSARI KECAMATAN TEMBALANG - Faiza Hawa; Rahmawati Sukmaningrum; A.B Prabowo; Sukma Nur Ardini (Universitas PGRI Semarang, 2014)
Abstract Being successful enterpreneur is everyone?óÔé¼Ôäós passion. Enterpreneurship can be an alternative way to reach prosperity in life. It needs to be noticed that it takes a lot of effort , passion, patience and creativity to be a succesful?é?á enterpreneur. So many people have great eagerness to be enterpreneur, but they have less knowledge to make it true. That becomes the reason why this training is given to them. It aims to train the people to be more knowledgeable in enterpreneurship. It also trains them to be more creative by recycling?é?á used things to valuable one. It is hoped that this training can be useful for them. They can practice what they have already got in the training in their life. They can produce may new things from the used thing around them and sell them around to make money without money. It will help them to be more prosperous for their financial. ?é?áFurthermore, it will help them to open more job vacancies. This training was acknowledged to the Young Islamic association, Mekarsari,?é?á in Rowosari village. This training provides the young people knowledge, creativity and new experience to create useful and valuable things. Keyword: enterpreneurship